Management of the tropical dry forests in Santa Elena Province: a conservation approach - Astudillo-Sánchez, Evelyng (2020)
Seasonally dry tropical forests are recognized for their biological and economic importance, as they possess a high number of endemic species and provide various ecosystem functions. However, the lack of a biodiversity conservation plan threatens comprehensive environmental management in the protected areas of Santa Elena Province, Ecuador. For this reason, a diagnosis was made in which conservation targets were identified to strengthen local environmental management capacity. Furthermore, Conservation Action Planning (CAP) and Strengths, Weaknesses, Opportunities and Threats (SWOT) methodologies were used to identify conservation priorities and resource management constraints. The analysis revealed technical-administrative flaws, and because of this an efficient approach to environmental management was sought. In addition, the garúa forest was recognized as a natural conservation target and the cabildo (community council) was recognized as a cultural conservation target. Participatory environmental governance needs to be strengthened to improve the management of protected areas.